REPRESENTASI FEMINISME DALAM FILM LIVE-ACTION MULAN - Silma Nadia; Ofi Hidayat (KAGANGA KOMUNIKA: Journal of Communication Science, 2022)
The live-action film Mulan is one of the war action films in which it describes gender equality. In addition, in this film there is also a depiction of the struggle of a girl who is determined to prosper her family until she has to go to war to replace her father. Women are not weak, women can stand on their own feet and women can play the role of men, is a representation of feminism that can be observed in several scenes in this film. This study was analyzed using Charles Sanders Peirce’s semiotics which focused on finding out what scenes represent feminism in the live-action film Mulan. The method used to research this Mulan Film is descriptive qualitative; the data collected is in the form of words and pictures, not in the form of numbers. Depictions of gender equality are presented in several scenes in this film, including Hua Mulan is endowed with strong chi, Mulan is a free spirited woman, Xianniang is another female figure with strong chi, feminism in the stereotype of ideal women, women can fight like a men and women can be a leaders, where each scene describes the flow of feminism.